Designers, visionaries and other stories : a collection of sustainable design essays - Chapman, Jonathan, 1974-; Gant, Nick (Earthscan, 2007)
"Designers, Visionaries and Other Stories unpacks the complex and crucial debates surrounding sustainable design to deliver a compelling manifesto for change, at a time of looming ecological crisis, mounting environmental legislation and limited progress. This is a book about sustainable design, by the leading sustainable design thinkers, for creative practitioners, professionals, students and academics. This challenging work provides the reader with a rich resource of future visions, critical propositions, creative ideas and design strategies for working towards a sustainable tomorrow, today."--Jacket